A novel LTE indoor location system based on multiple antenna clusters - Yajuan LV; Shan LIU; Rongyi HU; Wenhao ZHANG (Dianxin kexue)
With the rapid development of mobile internet services, demands of location service are becoming more diversified, then the location technologies become the key to satisfy the requirements. Long term evolution (LTE) indoor networks can solve the problem that GPS (global positioning system) signal can't arrive in indoor and provide high precision location service. However, LTE indoor location system need high precision synchronization among different base stations, and this is a new challenge for indoor network deployment. To solve the problem, a new LTE wireless location system based on multiple antenna clusters was proposed. The system could get TDOA(time difference of arrival) through uplink SRS (sounding reference signal) and it didn't need synchronization between different clusters which reduced the difficulty of network deployment. Then, a new location algorithm was designed which could support flexible antenna configuration. Finally, simulations and experimental measurements were given to verify the efficiency of the system and algorithm. Results show that meter indoor location accuracy can be realized.